Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis

Question de différence - Guillaumin, Colette (Questions Féministes, 1979)
La « différence » est une relation entre hommes et femmes qui assigne à l'un des groupes, celui des femmes, des obligations matérielles envers l'autre groupe ; imposées par des signes dans le corps (motricité entravée, vête-ments, usage de l'espace et du temps) elles nous à intérioriser la soumission et la disponibilité. La différence n'est ni « naturelle » ni bonne en soi. Conséquence banale de ce qui nous est imposé socialement, elle est l'expression de la relation de pouvoir entre hommes et femmes, Revendiquer un « droit à la différence » est acte d'allégeance au « Réfèrent » . Et qui est le Réfèrent ?
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; approches et analyses; corps; cours; discipline; europe; france; féminisme matérialiste; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques